Scenarios for transitioning cars from ICEV to BEVs and PHEVs using household level GPS travel data. (November 2020) - Ji, Wei; Tal, Gil
Highlights: PEV adoption can reduce greenhouse gas emission by up to 65% Optimal PEV model assignment at household level is significantly different from vehicle level. BEVs with 120+ miles range can benefit the most travel demand. The achievable GHG emission reduction decreases by 2/3 if PHEV drivers never charge. Abstract: There has been a continuous effort to quantify the expected greenhouse gas reductions from plug- in electric vehicles (PEVs). Most existing studies are based on standardized driving cycles to compare the performance of PEVs and conventional internal combustion engine (ICE) vehicles. This study is based on assigning the most efficient plug-in hybrid or full electric vehicle to a household based on the household travel behavior as collected by GPS tracking data of thousands of vehicles' real trips in California, and it found that PEV adoption can reduce greenhouse gas emission by up to 65%. We further explore the market share difference in assigning optimal vehicle models by considering vehicle-based and household-based travel demand, and we found that, given currently available technology, in many cases adoption of Plug-in Hybrid Electric vehicles (PHEVs) will not necessarily result in significantly higher greenhouse gas (GHG) emissions (2.8% higher) compared to battery electric vehicles (BEVs), while PHEVs have advantages to satisfy household's long-distance travel demand. However, if PHEV drivers never charge their vehicles, the achievable GHG emission reduction will be decreased by nearly 2/3.